Analisis Kontribusi Teman Dalam Tugas Kelompok Terhadap Tingkat Stres Mahasiswa Universitas Airlangga Selama Pandemi Covid-19 - Itsna Jannatul Kamilah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
The Covid-19 pandemic has become a global crisis, affecting millions of people across nearly all countries, including Indonesia. In response, the Indonesian government implemented a policy known as Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM), or Enforcing Restrictions on Community Activities. This policy significantly impacted various sectors, with the education sector being one of the most affected. Universities and schools were required to switch from traditional face-to-face learning to online distance learning. While this approach was necessary to reduce virus transmission, it posed numerous challenges for students, including issues related to mental health, academic pressure, and limited social interaction. One crucial factor that can influence students’ psychological well-being during such times is the role and contribution of peers within academic groups.This study aimed to examine the relationship between the contribution of friends in group work and the level of stress experienced by undergraduate students of Universitas Airlangga during the 2021/2022 academic year amidst the Covid-19 pandemic. This research employed an analytic observational study design with a cross-sectional approach. A total of 75 respondents were selected using a simple random sampling technique. Data were analyzed using the chi-square correlation test. The results revealed that there was no statistically significant relationship between gender and the contribution of group members with students' stress levels during the period of online learning. These findings suggest that other factors may play a more dominant role in influencing students’ psychological stress during remote education. Further studies are recommended to explore additional variables that may affect student stress during online learning environments in pandemic situations.